Thinking and Banal Evil in Arendt: Towards a New Interpretation - Irizar, Liliana (Anales del Seminario de Historia de la Filosofía, 2026)
This article disputes the notion of banal evil, understood as thoughtlessness or inability to think. The reasons are various. Arendt does not clarify how one arrives at the unfortunate state of thoughtlessness. There are also some confusing interpretations of banal evil. But more than that, the definition of banal evil contains a kind of contradictory thesis: that evil does not result from an inability to think, but from a failure to think morally correctly, in which the evil is hidden. According to St. Thomas, the causes of wrong moral thinking are passion, vice and ignorance. They are passion, vice, and ignorance. It is from this approach to banal evil that Arendt and St. Thomas can be articulated in harmony. Finally, a possible approach between the two philosophers from a metaphysical perspective on evil is discussed. It is worth noting that the article shows how much the debate on the meaning of banal evil is still alive.